CX3CR1: a potential microglia-specific PET imaging target in Alzheimer’s and Parkinson’s diseases - Yang, Hongzhi; Wang, Yanli; Xu, Yulong; Wang, Changning (Frontiers in Pharmacology, 2025)
Microglia are the resident immune cells of the central nervous system (CNS), playing a crucial role in maintaining brain homeostasis and mediating neuroimmune responses. The chemokine receptor CX3CR1, predominantly expressed on microglia, regulates microglial function via interactions with its neuronal ligand CX3CL1. The CX3CR1-CX3CL1 signaling exhibits complex, context-dependent roles in neurodegenerative diseases. In Alzheimer’s disease (AD) and Parkinson’s disease (PD) animal models, CX3CR1 deficiency shows paradoxical outcomes, attenuating or exacerbating amyloid-β (Aβ) and tau pathologies in AD, while consistently worsening α-synuclein-induced neurodegeneration in PD. Although CX3CR1 emerges as a promising therapeutic and diagnostic target, its complex role in microglial dynamics remains incompletely understood. Positron emission tomography (PET) imaging provides a powerful, noninvasive method for investigating biological processes in vivo. There is an urgent need to develop and validate new PET tracers targeting microglial CX3CR1 in the CNS, further offering new opportunities for the diagnosis and treatment of neuroinflammation-associated neurodegenerative diseases.